Potential therapeutic targets for hypoxia-induced pulmonary artery hypertension - Dong, Li (BioMed Central, 2014)
BACKGROUND: Hypoxic pulmonary artery hypertension (PAH) as a severe pulmonary disease is characterized by changes of pulmonary vascular reconstruction. Mitochondrial ATP-sensitive potassium channel (mitoK(ATP)) was considered as one of factors responsible for the proliferation of hypoxic pulmonary arterial smooth muscle cells (PASMCs), although the exact mechanisms remain unclear. METHODS: Pulmonary artery hypertension was induced in rats with or without 5-hydroxydecanoate (5-HD). The mean pulmonary artery pressure, morphologic changes, mRNA and protein expressions of voltage-gated potassium channels (Kv1.5 channel), were measured. The concentrations of monocyte chemo-attractant protein-1 (MCP-1) and transforming growth factor-beta1 (TGF-β1) were detected. Furthermore, pulmonary arterial smooth muscle cells (PASMCs) were isolated and cultured with or without hypoxia pretreated with or without 5-HD or/and Kv1.5 inhibitor 4-aminopyridine (4-AP). Mitochondrial membrane potential (Δψm) and the proliferation of PASMCs were detected. RESULTS: 5-HD significantly prevented the development of PAH by blocking the mitochondrial membrane depolarization, increased the expression of voltage-gated potassium channels, and reduced pulmonary hypertension mediated by TGF-β1 or MCP-1 signaling pathway. CONCLUSION: The MitoK(ATP) plays an important role in the development of PAH and may be therapeutic target for the treatment of disease.